2003
DOI: 10.1002/anie.200200541
|View full text |Cite
|
Sign up to set email alerts
|

Watching Photoinduced Chemistry and Molecular Energy Flow in Solution in Real Time

Abstract: Energized molecules are the essential actors in chemical transformations in solution. As the rearrangement of bonds requires a movement of nuclei, vibrational energy is often the driving force for a reaction. Vibrational energy can be redistributed within the "hot" molecule, or relaxation can occur when molecules interact. Both processes govern the rates, pathways, and quantum yields of chemical transformations in solution. Unfortunately, energy transfer and the breaking, formation, and rearrangement of bonds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 164 publications
4
63
2
1
Order By: Relevance
“…As a background of this model, recent experimental studies on IVR in solution indicated the IVR rates are well explained by such a hierarchical or tier model [1,[14][15][16][17][18]. In the tier model, the initial vibrational energy is not distributed over all the vibrational modes simultaneously, but flows through specific low-order couplings step by step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a background of this model, recent experimental studies on IVR in solution indicated the IVR rates are well explained by such a hierarchical or tier model [1,[14][15][16][17][18]. In the tier model, the initial vibrational energy is not distributed over all the vibrational modes simultaneously, but flows through specific low-order couplings step by step.…”
Section: Resultsmentioning
confidence: 99%
“…Flow of excess vibrational energy of molecules and solvation dynamics are closely related to each other, and play important roles in various photochemical reactions in condensed phases [1][2].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have sought to explore the relative importance of IVR and IET in excited molecules in solution, and both processes are commonly encapsulated in the general term, vibrational energy transfer (VET). 16,17 The timescales for VET are sensitively dependent on the mode of interest (isolated high frequency modes typically relax more slowly than low frequency vibrations) and on the strength of the solute-solvent interaction. 16 In the case of strongly interacting systems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Since these original studies, the field of femtochemistry has rapidly evolved and it is not the aim of this perspective to review this development. Rather, the reader is referred to a number of excellent articles, reviews and books that have appeared over the years (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%